Endoscopic transpapillary gallbladder stenting to prevent acute cholecystitis in patients receiving fully covered self-expandable metal stents for benign biliary stricture - Morgan Wong; Sergio A. Sánchez-Luna; Tarun Rustagi (Endoscopy International Open, 2021)
Background and study aims Fully covered self-expanding metal stents (FCSEMS) are being increasingly used for benign biliary strictures (BBS); however, they are associated with risk of acute cholecystitis. Prophylactic endoscopic transpapillary gallbladder stenting (ETPGBS) can facilitate continuous gallbladder drainage and prevent acute cholecystitis from occlusion of cystic duct orifice by the FCSEMS. The aim of this study was to assess the technical feasibility, efficacy, and safety of ETPGBS to prevent acute cholecystitis in patients receiving FCSEMS for BBS. Patients and methods This was a retrospective analysis of a prospectively collected database at a single center of all patients who underwent prophylactic ETPGBS with FCSEMS for BBS between December 1, 2016 and November 30, 2020. Results A total of 71 ETPGBS were placed during the study period. Sixteen patients (mean age: 66.4 ± 19.8 years; 81 % male) underwent ETPGBS prior to biliary FCSEMS during the same endoscopic session. FCSEMS were left in place (stent dwell time) for a median of 173 days (range: 69–473; mean 196 ± 121) with resolution of BBS and successful removal of ETPGBS and FCSEMS in 12 patients. There was significant improvement in total bilirubin level (5.25 ± 5.53 vs 0.94 ± 0.85 gm/dL; P = 0.008). No episodes of acute cholecystitis or any other post-procedural complications were noted during the median follow-up of 337 days (range: 150–856; mean 394 ± 236). Conclusions ETPGBS prevented stent-related acute cholecystitis with continued efficacy of FCSEMS for BBS.